La politique de communication ou comment gérer son image par des règles partagées - Siham Alaoui (Communiquer)
In a constantly changing socio-political environment, organizations tend to develop and maintain a good public image. This can be done by adopting a communication policy. This strategic tool allows to control communication flows both internally and externally, notably in a technological context affecting the circulation of information. The author examines the properties of this policy, the methods of its elaboration and its implementation.